Acupuncture in the Anesthetic Recovery of Bitches Submitted to Ovariohysterectomy - Amanda Caroline Gomes Graboschii; Carolina Carvalho dos Santos Lira; Jackellyne Laís Ferreira Lins; Marcia Kikuyo Notomi; Pierre Barnabé Escodro (Journal of Acupuncture & Meridian Studies, 2023)
Background : Cardiorespiratory depression caused by anesthesia decreases the quality and increases the time of postoperative recovery. The acupoint Governor Vessel 26 (GV26) is a resuscitation point that can reverse this depression and can be safely used without side effects. Objectives: The objective of this study was to evaluate the stimulation and anesthetic recovery time of GV26 in bitches submitted to ovariohysterectomy (OH) under dissociative anesthesia. Methods : As pre-anesthetic protocol, acepromazine 0.2% (0.1 mg/kg) and tramadol hydrochloride (2 mg/kg) was used, and induction was performed using midazolam (0.5 mg/kg) and ketamine (10 mg/kg). For the control group, standard procedure was performed for OH, with anesthetic recovery and post-surgical procedures. For the acupuncture group (AP), the stimulation of acupoint GV26 was performed 20 minutes after the anesthetic induction and maintained for 5 minutes. Respiratory rate, amplitude (superficial, normal or deep), type of respiratory movement (abdominal, abdominocostal or thoracoabdominal), heart rate, capillary filling time, temperature, presence or absence of laryngotracheal reflex, presence or absence of interdigital reflexes were assessed immediately before PAM application, and 2 (T1), 5 (T2), 10 (T3), 15 (T4), 20 (T5), 25 (T6) and 30 (T7) minutes after treatment. The results were tabulated and statistically analyzed. Results : When comparing the AP group with the control group, an improvement in amplitude of the chest cage was observed at all times, where the animals remained in normal or deep respiratory amplitude. The heart rate was significantly higher for the AP group (155.5 ± 34.4 bpm) than the control group at T1 (105.1 ± 15.4 bpm), while recovery time was lower for the AP group (54.1 ± 14.9 min) when compared to control group (79.9 ± 17.9 min). Conclusion : The present paper demonstrated the efficacy of GV26 in maintaining adequate respiratory amplitude and decreasing the anesthetic recovery time.